2017
DOI: 10.18616/is.v6i1.3021
|View full text |Cite
|
Sign up to set email alerts
|

Influência da residência multiprofissional na vida profissional de egressos

Abstract: O objetivo deste estudo foi analisar a influência da Residência Multiprofissional da Universidade do Extremo Sul Catarinense na vida profissional dos egressos, por meio de um estudo de delineamento transversal e análise descritiva. A amostra foi composta por 42 profissionais da saúde entre residentes egressos e amigos indicados que não realizaram a residência. Os dados foram coletados através de um questionário online, durante o período de novembro de 2014 a fevereiro de 2015. Verificou-se que a população de r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 4 publications
1
5
0
6
Order By: Relevance
“…In view of the significant number of graduates enrolled in teacher training, the Residence seems to promote, through the model of permanent education, teaching among graduates. 2,28 Thus, in articulating the knowledge to the research and the extension, by the course, in its residents, the need of the search of new knowledge, learning and other activities towards the continuity of the training. It is exposed in this direction that a recent study with graduates of the Multiprofessional Residency Program of the National Cancer Institute José Alencar Gomes da Silva, Lato Sensu level and technical level, showed that 57.3% of Lato Sensu respondents, after Residency, continued their studies, and of these, 15% included masters and doctorates, adding pathways to teaching and research.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the significant number of graduates enrolled in teacher training, the Residence seems to promote, through the model of permanent education, teaching among graduates. 2,28 Thus, in articulating the knowledge to the research and the extension, by the course, in its residents, the need of the search of new knowledge, learning and other activities towards the continuity of the training. It is exposed in this direction that a recent study with graduates of the Multiprofessional Residency Program of the National Cancer Institute José Alencar Gomes da Silva, Lato Sensu level and technical level, showed that 57.3% of Lato Sensu respondents, after Residency, continued their studies, and of these, 15% included masters and doctorates, adding pathways to teaching and research.…”
Section: Resultsmentioning
confidence: 99%
“…Portanto, observa-se que nas instituições de atuação da RMS há grande fluxo de pacientes com afecções ortopédicas e traumatológicas, sendo campos ricos em termos de conhecimentos e práticas de enfermagem. Nesse aspecto, o residente egresso tem um destaque em seu currículo, visto que possui formação de acordo com os princípios e diretrizes do SUS, com habilidades específicas, de acordo com as necessidades da região (Oliveira et al, 2017, Mello et al, 2021. Ademais, constatou-se a partir da vivência que a maior demanda de atendimento é composta por pacientes adultos jovens, do sexo masculino com histórico de acidente de motocicleta, com acometimento ortopédico principalmente relacionado a fraturas expostas e/ou fechada em membros inferiores.…”
Section: Atuação Do Enfermeiro Residente Em Ortopedia E Traumatologia...unclassified
“…Esse perfil da Residência prepara o profissional para ofertar um atendimento mais humanizado, focando não somente no estado de doença da pessoa, mas inter-relacionando com o meio em que está inserido. Assim, o profissional egresso da RMS tem um diferencial em seu currículo, visto que possui formação pautada nos valores e diretrizes propostos pelo SUS (OLIVEIRA et al, 2017).…”
Section: Percepções Dos Egressos X Expectativas Dos Ingressantesunclassified